Hygrothermal And Wear Behaviour Of Short Carbon Fiber Reinforced Polycarbonate - Othman, Ainnur Hanim (Universiti Sains Malaysia, 2018)
Four compositions with 0, 5, 10, and 15 % of short carbon fiber loading reinforced with polycarbonate was prepared using single screw extruder. The composite was then tested for the wear and hygrothermal behaviour. On the wear testing, it was found that the wear resistance depends on the carbon fiber loading. On the hygrothermal testing, specimens were immersed in water at room temperature and 60 °C until reached equilibrium in weight. It was found that diffusion coefficient also depend on fiber loading. As the fiber loading increased, the coefficient of diffusion reduced, means that it less absorb water. Then, the immersed sample was test with three points bending flexural testing on wet and redried samples. The observed flexural strength and modulus were these properties drop at wet condition and increased back upon recovery. The flexural properties at 60 °C were lower than room temperature. It can be proved that the high temperature tend to degrade composite faster than at room temperature.